Development of a Health Care Model for Home Bound Elder by Community Participation in Ubon Ratchathani, Thailand - มิลินจรูญพงษ์ นิธินันท์; ศรีสุภนันต์ มยุนา; จันทรโมรี สุรีย์; สุวรรณ ประภาเพ็ญ (Journal of The Royal Thai Army Nurses, 2018)
This research is a participatory action research (PAR) that applies community-based Approach. The purpose is to study and develop the health care model for the home bound elder by community participation in Ubon Ratchathani the sample group in Khemarat district was 40 community members or health network members and the home bound elder were 100 people, studied in February,2017–March,2018. The tools used were questionnaire, general information questionnaire for in-depth interview participatory assessment form the satisfaction rating and the quality of life assessment The research was approved by the ethics committee from Western University. Descriptive and inferential statistics for comparison of average scores before and after using Paired t-test and qualitative content analysis. The study was 2 spiral of development the health care model for the home bound elder by community participation comprised 1. There were community organizations established the elderly community 2. Public health team supports the knowledge and skills 3. Local government and district development will support welfare and care management 4. The discussion forum on elder care 5. Set up a multi-purpose center for the elderly in the community 6. Coordinate and cooperate network 7. Organize activities in the form of “community help community by community” by developing the potential of people of all ages in the community to care for the elderly. After the development of the model Average score Participation in development was higher than before development ( = 3.99, S.D. = 0.5). The results of the comparison between the mean scores of participatory development in the pre-development and post-development models were different. At the .05 level (t = 2.23, P-value <.05), the satisfaction of the community toward the model was found to be satisfactory at the high level. Satisfaction was increased ( = 37.88, S.D. = 6.66). The quality of life was at a moderate level ( = 68.74, S.D. = 8.22). The suggestion should be to provide an environment conducive to health care, promote health promotion, prevent disease and prevent complications from chronic diseases.